120 Pre-Slaughter Feed Acidification with Feed Grade Sodium Formate Reduces Microbial Abundance in Finishing Pigs. (10th April 2018) - Jendza, J A; Chen, H Y; Graham, A
Abstract: Forty-eight pigs were selected from a performance study looking at effect of different dosing regimens on animal performance in a commercial swine barn. As part of the performance trial, feed was treated with 0, 3, 6, or 9 g/kg of acidifier starting 2 weeks prior to first cuts (treatments 1, 2, 3, and 4). Fecal and cecal samples were collected 1 week prior to slaughter to ascertain the effect of feed acidification with feed grade sodium diformate (Amasil® NA) on microbial abundance. Digesta samples were analyzed for aerobic plate count (APC), Enterobacteriaceae, total coliforms, and E. coli by Eurofins Scientific (Des Moines, IA). Microbiology data (Log10 cfu/g) were analyzed by sampling site using JMP (13.1.0) according to a Generalized Linear Model, with a Poisson distribution and log link-function, with fixed effect of treatment. Single degree-of-freedom contrasts were used to compare each acidified treatment to the unacidified control (α = 0.05). Acidification with 3 and 6 g/kg tended to reduce cecal APC by 1.2 and 1.1 log10 cfu/g, respectively ( P = 0.07). Total coliforms, E. coli, and Enterobacteriaceae counts were decreased by 1.2 to 1.6, 1.3 to 1.7, and 1.6 log10 cfu/g, respectively, relative to the control ( P < 0.05). Feed acidification reduced colonic APC, total coliforms, E. coli and Enterobacteriaceae by between 1.3 to 1.9, 1.9 to 2.7, 3.0 to 3.9, and 1.8 to 2.6 log10 cfu/g, respectively, relative to the control ( P < 0.01). Results indicate that acidification of finisher feed in the weeks immediately pre-slaughter can reduce microbial load of pigs.